Development of Preclinical Models to Understand and Treat Colorectal Cancer - Sebolt-Leopold, Judith S. (Clinics in Colon and Rectal Surgery, 2018)
The establishment and validation of preclinical models that faithfully recapitulate the pathogenesis and treatment response of human colorectal cancer (CRC) is critical to expedient therapeutic advances in the clinical management of this disease. Integral to the application of precision medicine for patients diagnosed with metastatic CRC is the need to understand the molecular determinants of response for a given therapy. Preclinical models of CRC have proven invaluable in answering many of our basic questions relating to the molecular aberrations that drive colorectal tumor progression. This review will address the comparative merits and limitations of the broad spectrum of in vitro and in vivo models available for study of colorectal tumors and their response to experimental therapies.
Keywords: organoid; xenograft; genetically engineered mouse model